Perancangan Aplikasi Penentuan Pangkalan LPG Prioritas Penyaluran Tabung Gas Menggunakan Metode SMART pada PT Trindomas Inti Prima - Gilang Taruna; Alvino Octaviano (Jurnal Riset Informatika dan Inovasi, 2026)
The distribution of subsidized 3 kg LPG requires a targeted, efficient, and objective allocation process to ensure energy availability for the community. PT Trindomas Inti Prima continues to face challenges in determining priority LPG outlets due to a manual assessment process that is prone to subjectivity. This study aims to design a decision support system application to determine priority LPG distribution outlets using the Simple Multi-Attribute Rating Technique (SMART) method. The SMART method evaluates alternative outlets based on five main criteria: demand volume, stock availability, distribution distance, order frequency, and storage capacity. The research was conducted through stages of requirements analysis, system design using UML, web-based application implementation, and functional testing using the black-box method. The results indicate that the system is capable of generating objective, consistent, and transparent rankings of LPG outlets, thereby assisting management in making more effective and efficient distribution decisions.